Insulin/IGF1 signalling mediates the effects of β2‐adrenergic agonist on muscle proteostasis and growth. Issue 2 (1st April 2019) - Gonçalves, Dawit A.; Silveira, Wilian A.; Manfredi, Leandro H.; Graça, Flávia A.; Armani, Andrea; Bertaggia, Enrico; O´Neill, Brian T.; Lautherbach, Natalia; Machado, Juliano; Nogara, Leonardo; Pereira, Marcelo G.; Arcidiacono, Diletta; et al.
Abstract: Background: Stimulation of β2 ‐adrenoceptors can promote muscle hypertrophy and fibre type shift, and it can counteract atrophy and weakness. The underlying mechanisms remain elusive. Methods: Fed wild type (WT), 2‐day fasted WT, muscle‐specific insulin (INS) receptor (IR) knockout (M‐IR −/− ), and MKR mice were studied with regard to acute effects of the β2 ‐agonist formoterol (FOR) on protein metabolism and signalling events. MKR mice express a dominant negative IGF1 receptor, which blocks both INS/IGF1 signalling. All received one injection of FOR (300 μg kg −1 subcutaneously) or saline. Skeletal muscles and serum samples were analysed from 30 to 240 min. For the study of chronic effects of FOR on muscle plasticity and function as well as intracellular signalling pathways, fed WT and MKR mice were treated with formoterol (300 μg kg −1  day −1 ) for 30 days. Results: In fed and fasted mice, one injection of FOR inhibited autophagosome formation (LC3‐II content, 65%, P ≤  0.05) that was paralleled by an increase in serum INS levels (4‐fold to 25‐fold, P ≤  0.05) and the phosphorylation of Akt (4.4‐fold to 6.5‐fold, P ≤  0.05) and ERK1/2 (50% to two‐fold, P ≤  0.05). This led to the suppression (40–70%, P ≤  0.05) of the master regulators of atrophy, FoxOs, and the mRNA levels of their target genes. FOR enhanced (41%, P ≤  0.05) protein synthesis only in fed condition and stimulated (4.4‐fold to 35‐fold, P ≤  0.05) the prosynthetic Akt/mTOR/p70S6K pathway in both fed and fasted states. FOR effects on Akt signalling during fasting were blunted in both M‐IR −/− and MKR mice. Inhibition of proteolysis markers by FOR was prevented only in MKR mice. Blockade of PI3K/Akt axis and mTORC1, but not ERK1/2, in fasted mice also suppressed the acute FOR effects on proteolysis and autophagy. Chronic stimulation of β2 ‐adrenoceptors in fed WT mice increased body (11%, P ≤  0.05) and muscle (15%, P ≤  0.05) growth and downregulated atrophy‐related genes (30–40%, P ≤  0.05), but these effects were abolished in MKR mice. Increases in muscle force caused by FOR (WT, 24%, P ≤  0.05) were only partially impaired in MKR mice (12%, P ≤  0.05), and FOR‐induced slow‐to‐fast fibre type shift was not blocked at all in these animals. In MKR mice, FOR also restored the lower levels of muscle SDH activity to basal WT values and caused a marked reduction (57%, P ≤  0.05) in the number of centrally nucleated fibers. Conclusions: NS/IGF1 signalling is necessary for the anti‐proteolytic and hypertrophic effects of in vivo β2 ‐adrenergic stimulation and appears to mediate FOR‐induced enhancement of protein synthesis. INS/IGF1 signalling only partially contributes to gain in strength and does not mediate fibre type transition induced by FOR.